Comparative Analysis of Organic Waste Media on the Development and Nutrient Profile of Black Soldier Fly (Hermetia illucens) Larvae - Cacuk Setyo Sasmito; Listya Purnamasari; Joseph Flores dela Cruz; Desy Cahya Widianingrum; Amam Amam (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
Organic waste management remains a major environmental challenge, particularly in agricultural sectors. One promising sustainable approach is bioconversion using Black Soldier Fly (Hermetia illucens, BSF) larvae, which can transform organic waste into high-value biomass. This study aims to evaluate the effects of different waste inputs on the growth and nutritional composition of BSF larvae. The feed media consisted of P1 (broiler chicken excreta waste), P2 (red dragon fruit waste), P3 (white crystal guava waste), and P4 (california papaya waste). Larvae were analyzed based on growth, survival rate, larval body coloration, and nutrient content, including moisture, ash, crude fat, crude protein, and crude fiber using proximate analysis. After a 20-d bioconversion period, the highest harvest weights and survival rates were observed in treatments P2 and P4. Among the fruit-based substrates, P2 and P4 yielded the most favorable overall performance. However, crude protein content in P2 and P4 was lower than in P1, while moisture content was higher in P4. These findings indicate that papaya (P4) and dragon fruit (P2) waste show potential as alternative bioconversion media due to their ability to support adequate larval growth, biomass production, and nutrient content